Co-IVF for Same-Sex Female Couples - Getrajdman, Chloe; Lee, Joseph A.; Copperman, Alan B. (Seminars in Reproductive Medicine, 2017)
The utilization of assisted reproductive technology (ART), particularly by same-sex female couples (SSFCs), has increased over the past few decades. Alongside the increase in use by lesbian women, there has also been an increase in the number of available treatment options. The process by which SSFCs make the various decisions associated with conceiving and parenting, however, has been largely overlooked. This review provides an overview of the reproductive treatments available to lesbian women and specifically highlights the “biological” and “social” obstacles they must overcome on their journey to parenthood. This review also describes how a relatively novel treatment strategy, co-in vitro fertilization, can give couples greater flexibility and provide them with the unique opportunity of a shared biological motherhood.
Keywords: Same-sex female couples; lesbians; co-IVF; reproduction medicine; family building